Passive biometric electronic lock via UHF RFID - Xiang ZOU; Jinsong HAN; Yuhang QU; Jian XIAO; Xian XU (网络与信息安全学报)
A biometric lock design method was proposed based on the internal features of human body, namely PBLock.It used the backscattered RF signals to collect the impedance characteristics of human fingertips through the contact between human fingers and tags.The advantage of such authentication method is that the human impedance was not easy to be stolen, and it was fully integrated with the hardware characteristics of the device (RFID tags), which greatly increased the difficulty for the attacker to copy and clone.To ensure the availability and efficiency of the system, an optimization authentication mechanism was proposed by cutting tag antenna, which effectively improved the impedance sensitivity.Moreover, the feasibility of passive drive was discussed by using the electromagnetic energy advantage of RFID system.Through a large number of experimental evaluations, the authentication accuracy of PBLock can reach 96%, and the average time cost of a single authentication is 1.4 seconds.Some attack models were presented based on practical environment.The results show that PBLock can effectively prevent counterfeiting attack, impersonation attack and replay attack, which provides an opportunity for the secure application of new biometric electronic locks.